Carbon/graphene composite nanofiber yarns for highly sensitive strain sensors. (5th April 2018) - Yan, Tao; Wang, Zhe; Wang, Yi-Qi; Pan, Zhi-Juan
Highlights: The strain sensors were successfully fabricated using carbon/graphene composite nanofiber yarn. The strain sensor showed excellent stability. Gauge factors as high as 1700 were achieved. The strain sensor could accurately detect the subtle deformation. Graphical abstract: Abstract: In this work, flexible strain sensors were fabricated using carbon/graphene composites nanofiber yarn (CNY)/thermoplastic polyurethane (TPU). These flexible strain sensors exhibit excellent sensitivity and stability because of the continuity, brittleness, and high conductivity of the CNYs. When the number of yarns and substrate thickness were 4 and 129 μm respectively, the average gauge factor value was >1700 under an applied strain of 2%. Meanwhile, the strain sensor showed a high level of stability during 300 stretching–relaxation cycles. Moreover, the strain sensor could accurately detect subtle deformations. The working mechanism of the strain sensor was also analyzed during stretching using a resistance network model; there was very good agreement between the experimental and simulation results. Such flexible strain sensors can be easily incorporated onto the surfaces of textiles, and within electronics, for use in applications such as smart textiles and health monitoring.